Does Masturbation Frequency Effect Sperm Parameters? - Hasan Turgut; Güner Kemal Özgür (Journal of Urological Surgery)

(untitled)
Objective:To evaluate the relationship between male infertility and masturbation habits of patients who cannot provide a sperm sample.Materials and Methods:A total of 48 male patients aged 22-44 years who presented with complaints of primary infertility were included in the study. Patients who met the study criteria were requested to provide a spermiogram sample after a 3-7-days abstention from sexual relations. Sperm samples were surgically taken from patients who could not provide a sperm sample and pathology results of the samples from the testes were assessed. Patients with a surgically obtained sperm sample were named Group 1 and patients with no live cells found group 2. According to the parametric conditions of the data, the Independent Samples t-test or the Mann-Whitney U test were applied (p<0.05).Results:The rate of obtaining a sperm sample was statistically significantly higher in the group with a higher monthly frequency of masturbation. No significant difference was seen between the groups with respect to age (p=0.81). There was a statistical significant difference between the groups with respect to the number of masturbations per month (group 1: mean 4.0±1.3, group 2: mean 1.9±0.9) (p<0.001).Conclusion:The results of this study showed that there could be a relationship between the frequency of post-adolescent masturbation and azoospermia, although this relationship is not scientifically explained.